Upgrading food consumption structure and carbon emissions analysis under goals of carbon peak and carbon neutrality - MA Dayan; ZHANG Chaozheng; PAN Deng; WU Yongning (Zhongguo shipin weisheng zazhi, 2023)
ObjectiveBy analyzing the food consumption structure and carbon emissions among Chinese residents from 2014 to 2020， this study aims to provide scientific support for guiding residents towards adopting sustainable consumption patterns and achieving the dual carbon goals of carbon peak and carbon neutrality.MethodsThe study focuses on food consumption and extends to food-related carbon emissions. By using comprehensive food carbon emission coefficients and the life cycle assessment method， both direct and indirect carbon emissions caused by food consumption among Chinese residents were calculated， and the evolving trend of food-related carbon emissions is explored.ResultsThe food structure of Chinese residents increases year by year with the animal food consumption， and the greenhouse gas emissions also increase significantly. Under the hypothetical scenarios assuming gradual adjustments of food consumption structure to meet dietary guidelines by 2030， 2040 and 2050， the total greenhouse gas emissions are projected to peak in 2030， 2040 and 2049， respectively， with certain increases compared to the current level.ConclusionThe adjustment of food consumption structure in China has brought great pressure on carbon emission reduction. Based on the above results and conclusions， reasonable policy implications are proposed.